2019
DOI: 10.3390/cells8101242
|View full text |Cite
|
Sign up to set email alerts
|

Reduced DAXX Expression Is Associated with Reduced CD24 Expression in Colorectal Cancer

Abstract: The presence of an activating mutation of the Wnt/β-catenin signaling pathway is found in ~90% of colorectal cancer (CRC) cases. Death domain-associated protein (DAXX), a nuclear protein, interacts with β-catenin in CRC cells. We investigated DAXX expression in 106 matched sample pairs of CRC and adjacent normal tissue by Western blotting. This study evaluated DAXX expression and its clinical implications in CRC. The results revealed that DAXX expression was significantly lower in the patients with the positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Similarly, a study lead by Tzeng et al. demonstrated that DAXX suppresses Tcf4 transcriptional activity and induces G1 arrest of colon cancer cells, functions as tumor suppressor ( 127 ), and the knockdown of DAXX caused significant cell proliferation and promote metastasis ( 126 ). In PanNETs, DAXX/H3.3 complex suppresses target genes including Stanniocalcin 2 (STC2) by promoting H3K9me3 ( 129 ), suggesting that DAXX acts as a tumor suppressor.…”
Section: Daxx and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study lead by Tzeng et al. demonstrated that DAXX suppresses Tcf4 transcriptional activity and induces G1 arrest of colon cancer cells, functions as tumor suppressor ( 127 ), and the knockdown of DAXX caused significant cell proliferation and promote metastasis ( 126 ). In PanNETs, DAXX/H3.3 complex suppresses target genes including Stanniocalcin 2 (STC2) by promoting H3K9me3 ( 129 ), suggesting that DAXX acts as a tumor suppressor.…”
Section: Daxx and Cancermentioning
confidence: 99%
“…For example, DAXX is overexpressed in many types of cancer such as prostate cancer ( 118 , 120 , 130 ), ovarian cancer ( 121 , 122 ), gastric cancer ( 123 ), and gliomas ( 14 ). DAXX is downregulated in advanced gastric cancer ( 125 ) and human colon adenocarcinoma cells ( 126 , 127 ), lung cancer ( 128 ), and PanNETs ( 129 ). One study suggests that DAXX binds to anaphase promoting complex (APC) coactivators Cdc20 and Cdh1 to inhibit the degradation of APC, thereby promoting chromosome instability during prostate cancer development ( 118 ).…”
Section: Daxx and Cancermentioning
confidence: 99%
“…Chen [ 67 ] demonstrated that decreasing DAXX expression in the nucleus inhibits proliferation, migration, and invasion of GC cells, while elevated DAXX expression in the cytoplasm promotes migration and invasion. Based on the reported literature [ 69 , 70 , 72 ], the function of DAXX in CRC also appears to be contradictory. Chen [ 69 ] discovered that DAXX is expressed at a low level in CRC tissues and inhibits proliferation and migration.…”
Section: Histone Chaperones In Digestive Cancersmentioning
confidence: 99%
“…Considering its abundance in CRC tumorous stem cells it has been reported as putative marker for the detection of invasiveness and metastasis. Cluster differentiation 24 is an emerging biomarker for CRC ( 140 ). Overexpression of CD24 is affiliated with tumor differentiation, invasion metastasis ( 141 ).…”
Section: Micrornas As Master Regulator Of Stemness and Metastasismentioning
confidence: 99%